حركيات التحول الديمقراطي في الوطن العربي: قراءة في المؤثرات الدولية - مرزوقي, عمر (revue mofakir; No 10 (2014): مجلـــة المفكــر, 2018)
The Arab region did not come out of the attention of the international powers, this interest was each time translated to fit the objectives of these international actors and according to the balances and the historic privacy. with the beginning of the ninties,the Western strategies have taken a distinctive change which was linked to a major shifts in the world affairs. These changes were reflected in the political and the social life and posed number of challenges and commitments in front of the Arab societies, in their structure and the prospects of their developments. These challenges obliged many of the Arab regimes to select the choice of reformation and political pluralism to a reasonable degree.